State of Medical Mycology at German Academic Medical Centres: A Survey of the German‐Speaking Mycological Society (DMYKG) and the Paul‐Ehrlich‐Society for Chemotherapy (PEG). Issue 10 (7th July 2021) - Groll, Andreas H.; Gordon, Kathrin; Buchheidt, Dieter; Willinger, Birgit; Heinz, Werner J.; Kurzai, Oliver; Rickerts, Volker; Cornely, Oliver A.
Abstract: Background: Little is known about the infrastructure to translate advances in the management of patients at risk to develop invasive opportunistic fungal diseases. To assess the current state of Medical Mycology support in Germany, we conducted a survey among all 36 academic medical centres. Methods: The survey consisted of a 3‐pages questionnaire sent out in the first half of 2019. Information included details of infrastructure, education and teaching; consultation services and interdisciplinary conferences; research activities and participation in network groups; radiology, microbiology and pharmacology support; publication activity; and European Confederation for Medical Mycology (ECMM) Excellence Center designation, if assigned. Results: Information was returned from 24 centres (67%). Thirteen institutions (54%) reported an independent infectious disease, and two a separate Medical Mycology department (8%); a Medical Mycology working group was reported for nine institutions (38%). An infectious disease consultation service was existent in 16 institutions (67%) and a multidisciplinary conference in 13 (54%). Fifteen institutions reported a separate study office with activities in infectious disease studies (63%). Laboratory capability for fungal identification and susceptibility testing was confirmed by all 24 institutions; testing of galactomannan by 23 (96%), cryptococcal antigen by 21 (88%), ß‐D‐Glucan by 9 (38%), and panfungal and Pneumocystis PCR by 21 and 22 (88% and 92%), respectively. Therapeutic drug monitoring of voriconazole was reported to be available in 15 (63%) institutions with a turnaround of ≤24 h during weekdays in 10 (42%). Two of the 24 University hospitals (8%) reported ECMM Diamond Excellence Status. Conclusions: The results of this survey document the continuing need to improve the availability of specialised Medical Mycology support in German academic medical centres.